Study of a cement mortar with incorporation of PCM microcapsules - Félix, Mónica (2009)
The incorporation of phase change materials (PCM) in construction materials contributes to the reduction of the energy consummation i the buildings. The needs of heating and cooling systems can be reduced with the adequate use of PCM. Te benefits to the comfort inside buildings appear during the change of phase of the PCM. The transferences of energy that occur during the transitions solid-liquid and liquid-solid are generally the most used to help the acclimatization of the buildings. For that reason the PCM must be microencapsulated. The exterior of the microcapsules is made with a polymer. This study presents the mechanical properties of a cement mortar with the incorporation of 20%, 30% and 40% of microcapsules of PCM. The aim was to find the maximum percentage to be incorporated in a cement mortar to use in the interior coating of walls. With the incorporation of the PCM microcapsules the strength class of the reference mortar (0%) must be maintained. The results of the first series of tests showed an important decrease of the mechanical strengths and it was not possible to maintain the strength class of the mortar with PCM microcapsules. In the second series of tests the composition of the mortar was changed by the addition of 10% of cement CEM II 52,5. The results showed that incorporations of 20% and 30% of PCM microcapsules decrease the mechanical strengths but the values obtained are still inside the requisites of the European standard. Te incorporation of 20% of PCM microcapsules was possible maintaining the same strength class of the reference mortar.